Avaliação dos monócitos na Leishmaniose Tegumentar Americana - PEREIRA, Ledice Inacia de Araujo (2012)
American Tegumentary Leishmaniasis (ATL) is caused by Leishmania protozoan that infects mononuclear phagocytic cells leading to cutaneous or mucosal lesions. The mechanisms responsible for parasite control or persistence are not completely known. Human monocytes are blood cells subdivided into three subsets (classical, nonclassical and intermediate) according to the CD14 and CD16 expression that is associated with different phenotypical and functional characteristics. The aim of this study was to evaluate the profile of monocytes in ATL. First, it was analyzed the nonclassical monocytes (CD14loCD16+) and CD56+CD16+ NK cell frequencies in peripheral blood (by using flow cytometry) of a patient with diffuse cutaneous leishmaniasis (DCL) before, during and after immunochemotherapy (chemotherapy treatment together with L. (L.) amazonensis and L. (V.) braziliensis monovalent vaccines plus BCG). Then, in localized cutaneous leishmaniasis (LCL) patients (n = 32) and healthy donors, the three monocyte subsets (CD14hiCD16-, CD14hiCD16+, CD14loCD16+) were evaluated by flow cytometry; in the whole blood cultures we evaluated the expression of cytokines in CD14+ monocytes activated with lipopolysaccharide (LPS, by flow cytometry), and the secretion of proinflammatory (tumor necrosis factor, TNF) and antiinflammatory (interleukin 10, IL-10) after activation with Toll-like receptor agonists (TLR2 (Pam3Cys), TLR4 (LPS)) or L. (V.) braziliensis antigen (Ag; ELISA was used). In DCL patient it was detected an increase in non classical monocytes and NK cell frequencies probably associated to BCG stimulation, contributing to the clinical cure of several lesions caused by L. (L.) amazonensis. In LCL patients, the CD16+ monocyte subsets were increased before treatment. A similar TNF and IL-10 expression in CD14+ monocytes activated with LPS was found in patients and controls. It was not possible to identify which monocyte subpopulation was the responsible for the TNF or IL-10 production due to alterations of the percentages of each subset after LPS stimulation. Activation through TLR2, TLR4 or with Ag leads to a higher production of TNF but not IL-10 in whole blood cultures of patients than of controls. Whereas in healthy controls there was a positive correlation between TNF and IL-10 production after different stimulations (LPS, Pam3Cys and Ag), this was not observed in LCL patients, except for TLR2 stimulation. A positive correlation was detected between amount of TNF in serum or in activated-whole blood cultures and the number of cutaneous lesions. These results suggested that nonclassical monocytes can contribute to the control of infection in DCL patient, a clinical form in which patients do not present acquired cellular immune response. In this case, activation of innate cells as monocytes can cause lesion regression decreasing costs with medicines and improving the life quality of the patients. On the other hand, in LCL patients monocyte subsets and cytokine imbalance, especially with increase of nonclassical and intermediate monocytes (CD14loCD16+, CD14hiCD16+) and TNF, can contribute to leishmaniasis immunopathogenesis. To understand the role of monocyte subsets in ATL can open new avenues to the identification of biological markers of disease severity as well as new therapeutic targets to ATL treatment.